2010
DOI: 10.1002/jccs.201000084
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Efficient Amination of Organic Halides Catalyzed by Copper Sulfate in PEG1000‐DIL/Methylcyclohexane Temperature‐Dependent Biphasic System

Abstract: A simple, efficient, and environmentally friendly procedure for the amination of organic halides catalyzed by CuSO4·5H2O in PEG1000‐DIL/methylcyclohexane temperature‐dependent biphasic system is described. The product can be easily isolated by a simple decantation, and the catalytic system can be recycled and reused without loss of catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Tables 3 and 4 show that all para-, meta-, and ortho-substitutions on the aryl halide were tolerated under these reaction conditions. For example, the palladium-catalyzed C-N coupling of ortho-substituted aryl halides is difficult and is the major drawback of this method [59]. We showed that N-substituted methyl 3-amino-1-benzothiophene-2-carboxylates 3a-o can be obtained in moderate to high yields using activated aryl iodides as starting reagents.…”
Section: Entrymentioning
confidence: 99%
“…Tables 3 and 4 show that all para-, meta-, and ortho-substitutions on the aryl halide were tolerated under these reaction conditions. For example, the palladium-catalyzed C-N coupling of ortho-substituted aryl halides is difficult and is the major drawback of this method [59]. We showed that N-substituted methyl 3-amino-1-benzothiophene-2-carboxylates 3a-o can be obtained in moderate to high yields using activated aryl iodides as starting reagents.…”
Section: Entrymentioning
confidence: 99%
“…14,15 The combination of polyethylene glycol spacers and functionalized ionic liquids incorporates various attractive physical properties of the linkers and ionic liquids to the modified supported material. [16][17][18] The transfer of unique 'critical solution temperature' (CST) of PEG to PEG-functionalized DILs was observed as temperature-dependent biphasic material in an organic solvent and thus further studied as tunable phase separable catalysts in organic reactions. [19][20][21][22][23][24] As the solvent, they dissolve carbohydrates and polymers, 25 stabilize and activate protein or enzyme, 26 separate inorganic salts from aqueous solutions, 27 function as reductant and stabilizer for nanoparticle synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative analyses of HMF were performed by HPLC using a C18 -reverse phased column (200 mm × 4.6 mm) equipped with a UV detector (λ H M F = 284 nm) (Waters 2489). For the detection of HMF, a 10:90 (v/v) mixture of acetonitrile and water was used as the mobile phase at a flow rate of 0.6 mL/min.…”
mentioning
confidence: 99%